2023
DOI: 10.1155/2023/6535583
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping Mechanism among Students Residing in Private School Hostels

Abstract: Background. Mental health problems can significantly impact a student’s academic performance, career, health, and future if they are not identified and managed in time. The poor mental health of young people is a global problem, including in Nepal. However, the scenario of perceived stress among adolescent students residing in academic hostels is not explored in Nepal. Therefore, this study aimed at determining the prevalence of perceived stress with its associated predictors, experienced stressors, and coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…It may be that their parent's expectations are higher or high goals and targets for their successful careers. Shrestha et al (2023) reported that strict hostel rules, worries about the future, and language barriers also stress students. Bhattarai et al (2016) stated that living in a hostel is also reported to be associated with stress among adolescent students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that their parent's expectations are higher or high goals and targets for their successful careers. Shrestha et al (2023) reported that strict hostel rules, worries about the future, and language barriers also stress students. Bhattarai et al (2016) stated that living in a hostel is also reported to be associated with stress among adolescent students.…”
Section: Discussionmentioning
confidence: 99%
“…(Seyedfatemi, Tafreshi, & Hagani, 2007). Students from residential they want to adjust to different cultures, backgrounds, and areas that gather and stay; these all affect their curriculum performance (Shrestha et al, 2023).…”
Section: Issn 2522-1914 (Online) Fizicna Reabilitacia Ta Rekreacijno-...mentioning
confidence: 99%